Effectiveness Of Giving Additional Food With Stretching Exercise And Short Breaks On Work Fatique And Musculoskeletal Disorder Of Production Workers PT. Rekaindo Global Jasa - Heni Ratna Candrawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Work fatigue and musculoskeletal disorder lead to work accidents, and decreased work productivity. Additional food, short breaks and stretching exercises can reduce work fatigue and musculoskeletal disorder. The purpose of this study was to determine the effect of additional food along with stretching and short resting exercises on work fatigue and musculosksletal disorder at PT. Rekaindo Global Jasa Production Section. This research method uses True Experiment with Non Equivalent pretest posttest Control Group Design. The sample was 52 production section workers. The Nordic Body Map questionnaire was used to measure musculoskeletal disorder and the Subjective Selft Rating Test Questionnaire was used to measure work fatigue. Data were tested by t-paired test and ANOVA test with significance level α = 0.005. The results of work fatigue research in treatment group 1 showed p value = 0.002 and treatment group 2 p value = 0.003, which means there were differences in work fatigue before and after treatment. The results of the musculoskeletal disorder treatment group 1 showed p value 0,000 and treatment group 2 p value = 0,000 which means there were differences in musculoskeletal disorder before and after treatment. The research results of work fatigue between groups showed p value = 0.012 which means there was a difference in work fatigue between the control and treatment groups. While the study of musculoskeletal disorder between groups p value = 0.001 which means there are differences in musculoskeletal disorder between the control and treatment groups. Analysis of the results of the study showed supplementation, short breaks and stretching exercises could reduce work fatigue and musculoskeletal disorder. Therefore supplementation with supplementary stretching and short breaks in the production workers of PT. Rekaindo Global Jasa need to be provided to reduce work fatigue and musculoskeletal disorder of production workers in PT. Rekaindo Global Jasa